PR Strategy for Island Beach Pisang Tourism Destination - Pradini, Gagih; Awaloedin, Dipa Teruna; Soraya, Zahra; Andini, Davi Ayu (CV ODIS, 2024)
Indonesia, an archipelagic country with 17,508 islands and an 81,000 km coastline, possesses coastal areas rich in natural resources. Despite this richness, effective utilisation and development of coastal and marine regions remain challenging. This study focuses on Banana Island, part of Lampung Province, addressing its potential as a tourist attraction. Acknowledging the need for strategic development, the study emphasises government involvement, facility provision, and promotional efforts. The role of Public Relations Marketing, precisely the three-pronged approach of pull, push, and pass strategies employed by the West Coast Tourism Office, is examined. The study aims to comprehend the impact of these strategies on Banana Island's tourism development, evaluating visibility, popularity, and overall appeal. Methodologically, qualitative research, descriptive analysis, and SWOT analysis are applied for a comprehensive understanding. Findings highlight marine attractions, community expectations, and transportation challenges. The success of the push strategy is evident in increased tourist visits. Suggestions include enhancing collaboration, regular social media updates, and coordinated platform posts.